Pemberdayaan Anak Yatim Melalui Pendampingan Intensif Pembelajaran Kitab Kuning di Panti Asuhan Sunan Kalijaga Malang - Sodikin Sodikin; Lilik Aminah; Siti Yumnah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program (PkM) was carried out at the Sunan Kalijaga Orphanage in Malang with the aim of empowering orphans through intensive mentoring in classical Islamic text (kitab kuning) learning. The program was motivated by the limited religious literacy among the orphans, particularly their difficulty in understanding traditional Islamic texts due to insufficient access to comprehensive religious education. The method employed was Participatory Action Research (PAR), which actively involved caregivers, tutors, and the orphans in all stages of the activity—problem identification, planning, implementation, reflection, and follow-up. The mentoring process was conducted collaboratively using bandongan and sorogan methods, combined with a contextual learning approach emphasizing textual comprehension and the strengthening of Islamic character. The results show a significant improvement in the orphans’ ability to read and understand classical Islamic texts, along with an increase in motivation and self-confidence in studying religious sciences. Furthermore, the program successfully established an internal learning community as a strategy for program sustainability. The collaboration between lecturers, students, and orphanage caregivers created a positive synergy in developing religious education and social empowerment. Overall, this program serves as an implementable model for orphan empowerment based on religious literacy that can be replicated in other social and religious institutions.